The Efforts to Improve Quality Mental Health Resilience for Generation Z Affected by Social Media - Fidiyani, Rini; Nuzulia, Siti; Riyatno, Riyatno; Putri, Debby Annisa; Wardana, Sefian Dwi Sukma (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: Indonesia, with a population reaching 278.69 million by mid-2023, is among the most densely populated countries in the world. Since the post-COVID-19 era, the number of mental health issues among Generation Z has increased significantly, with 671 reported suicide cases and 5,116 suicide attempts recorded by Statistics Indonesia (BPS) in 2020. This alarming trend highlights the urgent need to initiate community service movements targeting the productive age group, particularly Generation Z. One such initiative was carried out at the Institut Teknologi Telekomunikasi Purwokerto, where students primarily focus on the field of information technology.Purposes of The Devotion: The aim of this community service is to provide outreach and education to students, representing Generation Z, in order to foster quality mental health resilience in the global era.Method of The Devotion: The method consists of a preliminary survey, site visits, and socialization-education sessions, accompanied by discussions using respondent questionnaires to collect relevant feedback.Results Main Findings of the Devotion: It is at the heart of a research Social media offers numerous benefits; however, excessive use has a negative impact on psychological well-being, raising concerns about the mental health of Generation Z. Recommended efforts include collaboration with academics, government bodies, and NGOs to implement: a) Education and literacy programs for Generation Z; b) Counseling and advocacy support; c) Self-awareness development to manage social media usage.